Comparison of structure and composition of a fossil Champsosaurus vertebra with modern Crocodylidae vertebrae: A multi-instrumental approach. (April 2020) - Wöss, C.; Unterberger, S.H.; Degenhart, G.; Akolkar, A.; Traxl, R.; Kuhn, V.; Schirmer, M.; Pallua, A.K.; Tappert, R.; Pallua, J.D.
Abstract: Information on the adaptation of bone structures during evolution is rare since histological data are limited. Micro- and nano-computed tomography of a fossilized vertebra from Champsosaurus sp., which has an estimated age of 70–73 million years, revealed lower porosity and higher bone density compared to modern Crocodylidae vertebrae. Mid-infrared reflectance and energy dispersive X-ray mapping excluded a petrification process, and demonstrated a typical carbonate apatite distribution, confirming histology in light- and electron microscopy of the preserved vertebra. As a consequence of this evolutionary process, the two vertebrae of modern Crocodylidae show reduced overall stiffness in the finite element analysis simulation compared to the fossilized Champsosaurus sp. vertebra, with predominant stiffness along the longitudinal z-axes. Highlights: Characterization of a Champsosaurus vertebra from macro to micro length scales with a 'novel extended molecular imaging platform' (NEMIP). NEMIP combines micro-CT, nano-CT, MIR reflectance microscopic imaging, light microscopy, scanning electron microscopy, and energy-dispersive X-ray mapping followed by data analysis methods. Finite element analysis simulations were used to estimate the functional performance of the characterized bones. NEMIP revealed a more compact structure with lower porosity and higher bone density in a fossilized, carbonate apatite containing vertebra.